Role of nanoparticles in growth and development ofplants: A Review - AREEBA FAROOQUI,; HEENA TABASSUM,; ASAD AHMAD,; ABDUL MABOOD,; ADNAN AHMAD,; IFFAT ZAREEEN AHMAD, (International Journal of Pharma and Bio Sciences, 2016)
Nanotechnology is the most novel field of 21st century. Nanotechnology has the ability to transform the agricultural and food industry with the help of various innovative tools for the molecular management of diseases, rapid disease detection, enhancing the ability of plants to absorb nutrients. Nanotechnology has the potential to increase yield of nutrient values and also plays a vital role in developing improved systems for monitoring ecological conditions and increasing the capacity of crops to absorb nutrients or pesticides. There are majority of nano-material which is known for its plant growth promoting effects. This paper reportedly contains the key role of nanoparticles in plants. This present review highlights the effects of nanoparticles on growth, flowering and seed production in plants. Recent researches on effects of nanoparticles on various plant crops have reported for an increased germination and growth of seed. The aim of this project is to study the roles of nanoparticles on various plants. Effects of these nanoparticles on plant growth and development can be easily highlighted in this review